The Philosomer - Anthony Gritten (Performance Philosophy)
A decade on from its founding, it is the right time to take stock and consider the manner of Performance Philosophy’s constitution and its projection into and onto the world. There are questions about how it narrates itself, both inwardly to its network (though the global reach of Performance Philosophy suggests that ‘inward’ is not the right word here) and outwardly towards interlocutors nominally outside the network. One challenge concerns the “performative materialisation” of Performance Philosophy’s many practitioners. This can be unpacked with a few questions: Who witnesses events? Who intervenes materially? Who contributes to the network? Whose collaboration increases social capital? Who evaluates practitioners’ self-management? Other questions are possible. This essay considers some of these questions.